The potential of Speech-to-text technology in enhancing efficiency in the aviation sector in South Africa - Mainganya, Kagiso C. (University of the Witwatersrand, Johannesburg, 2024)
This research report evaluates the potential of speech-to-text technology to enhance efficiency in the aviation sector in South Africa. It examines how this technology could improve operational and flight efficiency, impact customer service, and address potential implementation barriers. Key focus areas include - the accuracy of speech- to-text conversion, especially in noisy environments like cockpits and air traffic control towers as well as, the technology's ability to adapt to various accents and aviation- specific jargon. The report also highlights the urgency of cybersecurity measures to protect sensitive flight data. A thematic analysis was conducted with a focus on dynamic capabilities and the General Systems Theory framework
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Customer service; Operational efficiency; Aviation sector in South Africa; Speech-to-text technology; UCTD; SDG-8: Decent work and economic growth